Desenvolvimento de farinha do subproduto da amêndoa de babaçu (Attalea speciosa Mart.), rica em fibra alimentar, para formulação de alimentos - Silveira, Maico da Silva (2023)
The kernel of Orbignya speciosa, known as babassu, plays a crucial role in agroextractive communities in the North and Northeast regions of Brazil. The processing of the kernel results in a by-product with high dietary fiber content, mainly insoluble fibers. Therefore, the objective of this study was to establish the processing conditions to obtain a flour rich in dietary fiber from this agroindustrial by-product, aiming at the application in food product formulations. The almonds were processed, and the by-product went through aqueous extraction and heat treatment steps to reduce the microbial load. Then, it was subjected to a drying process until it reached a moisture content of less than 10% and, finally, it was crushed, resulting in babassu almond flour (FAB), which was packed in plastic bags. Stability during storage was evaluated up to six months at room temperature (28 ± 2°C/ %UR) and two months at accelerated conditions (40 ± 2°C/ 85% RH). Analyses of proximate composition, dietary fiber, physical characteristics (pH, total acidity, water activity, color and electron microscopy) were performed. A focus group study was also conducted to identify terms associated with FAB, and the application in formulations of hamburger and mortadella analogs was tested, with proportions of 0%, 12%, 18%, and 24% of FAB. Sensory tests of acceptance, purchase intention, Check-All-That-Apply (CATA) and Rate-All-That-Apply (RATA) were applied to the formulated products. The yield of the FAB process was 40.3%, with a composition of 1.3% moisture, 45.8% lipids, 1.1% ash, 4.4% crude protein and 47.4 g.100g-1 total carbohydrates, highlighting the high content of insoluble dietary fiber (41.4g.100g-1 ). The flour remained stable for more than six months. The use of FAB in hamburger and mortadella analogs formulations, with the addition of 12% and 18% of FAB presented scores between 6 (I liked it slightly) and 7 (I liked it moderately) for the sensory attributes of overall acceptability, color, aroma, texture and flavor. The process of obtaining the fiber-rich ingredient showed a yield close to 40%, with a shelf life of more than six months, and can be used in formulations of vegetable products analogous to meat, such as hamburger and mortadella, at levels of 12 to 18%. Therefore, babassu kernel flour can be introduced into the market as a food ingredient, adding value to the processing of the fruit and assisting in the economic sustainability of babassu coconut agroindustry’s and extractive communities.